Fundamentals of financial accounting - Phillips, Fred
Fundamentals of Financial Accounting, presents an engaging, balanced, and appropriately paced analysis of the fundamentals of financial accounting. Its writing style makes it easy to read and understand, while the selection of real focus companies reinforces the relevance of accounting by introducing students to accounting and business activities in the context of their favorite companies